Influence of Literary Figures on Urdu Poetry of Azad Kashmir: A Study - DR. MUHAMMAD YOUSAF; DR. AMBREEN KHAWJA (دریافت)
The study of the influence of literary figures on the poetry of Azad Kashmir shows that there are influences of Sanskrit, Kashmiri, Persian, Arabic, Urdu and other regional languages ​​as well as classical and modern poetry on the literature of Azad Kashmir. There are intellectual and artistic influences on the poetry of Azad Kashmir from to the present period. Some thought is prominent, some artistic imitation is visible. There is similar style; there is also the use of similar tone. However, all these influences despite this, the poetry of Azad Kashmir have its own individuality and its own style. Azad Kashmir's poetic capital, while being a part of the poetic tradition of Urdu language, has interesting, unique experiences and individual characteristics in terms of theme, theme, style innovation, new symbols, techniques, untouched and unique creative experiences and many other aspects. Azad Kashmir's own regional symbols and some unique experiences give its distinctive color to the poets of Azad Kashmir. Happily, the influence of movements, ideologies and personalities in the footsteps is less visible in the new generation. The poets of the new generation are actively and diligently engaged in creating their own special point of view, their own tone, their own style, and their own color. In spite of the influence of literary movements, critical schools, literary theories, poetic styles and poet personalities in the poetry of Azad Kashmir, its own color and harmony exist with all the beauty, rather, the colors and styles of the poets of Azad Kashmir are different from those of many other regions.